1937
DOI: 10.1121/1.1915922
|View full text |Cite
|
Sign up to set email alerts
|

Sound Waves in a Moving Medium

Abstract: A theoretical approach is made to the problem of the behavior of sound waves in a pipe through which the medium is moving in a unidirectional flow with uniform velocity V. Calculation indicates the resonances of pipes to be affected by the steady flow so that the resonance peaks are flattened, while the separation between nodal points is reduced by the factor 1 − (V/c)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1938
1938
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, in practice it is generally found that the wider the bandwidth, the smaller the difference in the time delay estimates, so the condition given in Eq. (16) was found to be met in all the measurements reported in this paper. More details are given in the next section.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…However, in practice it is generally found that the wider the bandwidth, the smaller the difference in the time delay estimates, so the condition given in Eq. (16) was found to be met in all the measurements reported in this paper. More details are given in the next section.…”
mentioning
confidence: 51%
“…It has been found in practice that the wave which carries the leak noise in plastic pipes is predominantly a fluid-wave that is strongly coupled to the radial motion of the pipewall [10,15]. Because the flow speed of the water in the pipe is much less than the speed of the leak noise, it has a negligible effect [16], so the wave-speed in one direction should, in principle, be similar to the wave-speed in the other direction.…”
Section: An Overview Of Leak Detection Using Acoustic Correlationmentioning
confidence: 98%
“…A problem suggesting itself to Trimmer (34) by the silencers of motor cars is that of the propagation of sounds along a conduit in which the gas is moving with uniform velocity. He shows that, under the conditions which apply in practice, if a small particle velocity is superposed on a large drift velocity U, a velocity-potential of the type may be postulated in.which c, = c + U ; c2 = c -U and c is the velocity of sound in still air.…”
mentioning
confidence: 99%